The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2023
DOI: 10.3390/foods12173146
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating Factors Explaining U.S. Consumers’ Behavioral Intentions toward Irradiated Ground Beef

Jean A. Parrella,
Holli R. Leggette,
Peng Lu
et al.

Abstract: Although food irradiation is deemed safe and endorsed by health-related organizations worldwide, consumers are reluctant to accept the technology. Yet, consumer acceptance is critical as food irradiation has significant potential for increasing the safety and availability of food globally. To communicate about food irradiation, science communicators should understand the psychology behind consumers’ decision making related to irradiated foods. Using empirical research, we developed a theoretical model and used… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 89 publications
0
0
0
Order By: Relevance
“…Consequently, many consumers lack information or hold misconceptions about food irradiation, frequently equating it with radioactivity ( 10 ). Previous research has demonstrated a dearth of consumer knowledge regarding food irradiation, with a significant portion of survey respondents acknowledging their unfamiliarity with irradiated foods ( 11 , 12 ). This deficiency in knowledge has led to a cautious stance among consumers, highlighting the necessity for comprehensive nationwide education on food irradiation technology ( 10 ).…”
Section: Introductionmentioning
confidence: 99%
“…Consequently, many consumers lack information or hold misconceptions about food irradiation, frequently equating it with radioactivity ( 10 ). Previous research has demonstrated a dearth of consumer knowledge regarding food irradiation, with a significant portion of survey respondents acknowledging their unfamiliarity with irradiated foods ( 11 , 12 ). This deficiency in knowledge has led to a cautious stance among consumers, highlighting the necessity for comprehensive nationwide education on food irradiation technology ( 10 ).…”
Section: Introductionmentioning
confidence: 99%